Experimental Study on Prevention of Calcium Carbonate Crystallizing in Drainage Pipe of Tunnel Engineering - Yuanfu Zhou; Xuefu Zhang; Liangwen Wei; Shiyang Liu; Bin Zhang; Chao Zhou (Advances in Civil Engineering)
If the tunnel drainage pipes are blocked, the supporting structures will be in danger because they would receive more force than before. In order to investigate the blocking problem, some laboratory tests and in situ experiments were carried out. Microtests showed that the main component of crystal is calcium carbonate. Calcium ions, carbonate ions, and bicarbonate ions of groundwater should be related to the crystal. The polyvinyl chloride pipe, hydrophobic antistatic self-cleaning coated pipe, silicone rubber coated pipe, pipe under electromagnetic field, polytetrafluoroethylene coated pipe, and polyethylene coated pipe were used in laboratory and field experiments. The laboratory results showed that the electromagnetic field may be the best method to prevent crystallization because the crystallizing weight was less than 0.1 g in 30 days. The field tests showed that there was less crystals on the inner surface of hydrophobic antistatic self-cleaning coated pipe than that of the polyvinyl chloride pipe and the polytetrafluoroethylene coated pipe. The crystallization prevention effects of the other experimental pipes need more studies to examine.